Comparativo de la calidad de vida del adulto mayor. Medellín, 2008 (2010)
ABSTRACT: Compare the quality of life of older adults in Medellin with two groups. Methodology: comparative descriptive study of secondary information source, using the 82,601 records in the Quality of Life Survey of 2008, distributed into three groups: youth, adults and seniors. The analysis was univariate and bivariate, the demographic, economic, social and health security, together with statistical tests of association. Results: older adults account for 9.2%, with female advantage, marital status was married, with a marked difference in the condition of widowhood and 39% did not record any education. Economically it was found that 34.7% engaged in the home, 34.1% are retired and 9.5% continues to work with an average income of a minimum wage. The 71.4% is affiliated to the contributive regime, preventive medical consultations take place at higher rates than young and 31.3% do not. Only 7.3% fell ill last month and his sufferings were hypertension, stress and depression. Conclusions: the older adult with no differences against the other two groups, but age makes it more vulnerable in economic and health conditions have limited the access to opportunities, by not acceding to the demands that the means of production and society require, forgetting their experience and wisdom gained in the course of his life.